The Influence of Work Commitment and Work Motivation on the Performance of Population and Civil Registration Service Employees in South Papua Province: The Mediating Role of Work Discipline - Totok Sudarmanto; Meinarni Asnawi; Sandra Sukmaning Adji (Britain International for Academic Research (BIAR-Publisher), 2023)
This study delves into the intricate relationship between work commitment, work motivation, and employee performance, with work discipline serving as a mediating factor. Employing a quantitative research approach and causality analysis, a questionnaire was administered to all employees of the Population and Civil Registration Service in South Papua Province, encompassing Merauke, Boven Digoel, Mappi, and Asmat Regencies. Out of the 220 questionnaires distributed, 214 yielded valid responses suitable for data analysis. SEM-PLS analysis was utilized for hypothesis testing. The findings reveal a positive and significant influence of work commitment and work motivation on work discipline. Furthermore, work commitment, work motivation, and work discipline all demonstrate a positive impact on employee performance. Notably, work discipline effectively mediates the relationship between work commitment and work motivation on employee performance. This study delves into the intricate relationship between work commitment, work motivation, and employee performance, with work discipline serving as a mediating factor. Employing a quantitative research approach and causality analysis, a questionnaire was administered to all employees of the Population and Civil Registration Service in South Papua Province, encompassing Merauke, Boven Digoel, Mappi, and Asmat Regencies. Out of the 220 questionnaires distributed, 214 yielded valid responses suitable for data analysis. SEM-PLS analysis was utilized for hypothesis testing. The findings reveal a positive and significant influence of work commitment and work motivation on work discipline. Furthermore, work commitment, work motivation, and work discipline all demonstrate a positive impact on employee performance. Notably, work discipline effectively mediates the relationship between work commitment and work motivation on employee performance.